Critically Commenting Publics as Authoritarian Input Institutions: How Citizens Comment Beneath their News in Azerbaijan, Russia, and Turkmenistan. (12th March 2021) - Toepfl, Florian; Litvinenko, Anna
ABSTRACT: Little is known presently about how, why, and with what consequences audiences comment on their news in contemporary authoritarian regimes. In order to address this gap, this study leverages recent theorizing about the multiple public sphere under non-democratic rule. Accordingly, critically commenting publics are theorized as "input institutions" that not only create risks but also offer important benefits for autocrats. Grounded in this approach, the study develops a series of hypotheses about the extent of political criticism that should be visible beneath the news in three purposefully selected authoritarian contexts: Azerbaijan, Russia, and Turkmenistan. In order to test these hypotheses, commenting environments facilitated (or not) by 46 leading news organizations on seven platforms were considered (N=322). For each environment, coders established whether comments were published that were (1) critical of the autocrat himself, (2) critical only of lower-level policies or officials of the regime, or (3) entirely uncritical. As the findings show, the extent of readers' criticism differed systematically between the three contexts, broadly following the patterns hypothesized. Moreover, in line with this study's key assumptions, critically commenting publics were facilitated not only by opposition media but also by substantial numbers of state-controlled news organizations.